Revised calcareous nannofossil biostratigraphy of the Cenomanian/Turonian boundary: implications for global correlations and timescales - E. Erba; F. Russo; C. Bottini; G. Faucher (Società Geologica Italiana, 2014)
Calcareous nannofossil biostratigraphy is proven to be a reliable toll for dating and correlating Upper Cretaceous sequences at regional and global scale. Although high-resolution biozonations are available for the Cenomanian/Turonian boundary interval, assessment of nannofossil event reproducibility still demands detail investigations of different oceanic basins, paleolatitudes and settings. The Cenomanian/Turonian stage boundary is characterized by an ample C isotopic excursion marking the Oceanic Anoxic Event (OAE) 2. Thus nannofossil biozonation is often used to constrain the latest Cenomanian C istopic anomaly and the anoxic interval of enhanced burial of organic matter. We selected pelagic and hemipelagic sections from the Tethys, Pacific, Indian, Atlantic Oceans and the Western Interior Basin. Section selection was based on availability of stratigraphic data (e.g. isotopic stratigraphy and planktonic foraminifera biostratigraphy). The correlation among the studied sections shows that only five nanofossil bioevents occur, relative to the δ13C curve, at the same stratigraphic position. They are: the LOs of C. kennedyi, A. albianus, L. acutus, H. chiastia and the FO of Q. gartneri, the same five events reported in the GSSP section. Additional zonal and subzonal markers and a secondary bioevent reported in the three Cretaceous zonations were recognized. However, R. biarcus and C. striatus are too rare to be suitable as global biostratigraphic markers, whilst the FOs of Q. intermedium-5, E. octopetalus and E. eptapetalus have been found at different stratigraphic levels in the studied sections and in previous studies. Our results prove that nannofossil biostratigraphy is extremely useful for identification of the Cenomanian/Turonian boundary and constraining OAE2 at global scale.